2012
DOI: 10.1007/s00595-012-0364-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery in the management of mild gallstone pancreatitis: a prospective cohort study

Abstract: PurposeThe aim of this study was to establish enhanced recovery protocols for the management of mild gallstone pancreatitis.MethodsSixty consecutive patients were divided into enhanced recovery and traditional recovery (TR) groups in a randomized observational study. The basic enhanced recovery elements included early laparoscopic cholecystectomy, restrictive endoscopic intervention, and early oral nutrition. The incidence of complications, readmission, length of stay, and total medical cost were analyzed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A total of 24 studies reported recovery outcomes measured within 30 days after surgery. Only two articles reported recovery outcomes at 60 days after surgery, one study at 90 days, and ten studies did not specify the follow‐up duration. Baseline measures were reported in 21 of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 24 studies reported recovery outcomes measured within 30 days after surgery. Only two articles reported recovery outcomes at 60 days after surgery, one study at 90 days, and ten studies did not specify the follow‐up duration. Baseline measures were reported in 21 of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Other outcomes reported included cost 26,30,35,36,44,49,50,59 , pathway adherence 34,39,47 and patient satisfaction 25,34,40,42,43,49 . Many studies reported 'outcomes' related to compliance with processes of care, such as time to removal of the urinary drainage catheter and outcomes related to intravenous fluid administration (either total volume infused or time to discontinuation).…”
Section: Other Reported Outcomesmentioning
confidence: 99%
“…The population included in this study was exclusively composed of patients with acute biliary pancreatitis, considered in the Mediterranean countries, the most common etiology [ 2 ]. Since the gallstones etiology is the most frequent cause of AP in these countries, and although differences are recognized between the various etiologies of AP, there are few studies aimed at this subtype of patient population [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we defined the node with 72 hours as an early group and conducted a meta-analysis of the included literature. The results showed that the early surgery group did not experience increased postoperative complications [12,1416,18,2023,25,2728] (RR = 0.86; 95% CI = 0.56–1.32; P = .49) and conversion to open surgery [12,1416,18,2023,25,27] (RR = 0.84; 95% CI = 0.37–1.91; P = .68) compared with delayed surgery.…”
Section: Discussionmentioning
confidence: 99%